2015
DOI: 10.1016/s0924-9338(15)30576-9
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Feelings of Loneliness: Prevalence, Risk Factors and Longitudinal Associations with Depressive Symptoms and Child Adjustment

Abstract: IntroductionIn earlier studies, loneliness strongly correlates with depression and depressive symptoms. Longitudinal studies are rare.ObjectivesThe aim of the study was to investigate in a longitudinal setting the prevalence and risk factors of maternal loneliness as well as the associations between maternal loneliness, depressive symptoms and child's subsequent psychosocial adjustment.MethodsMothers’ reports of loneliness were explored in a sample of 133 mothers during pregnancy (T1) and when the firstborns w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…This will have a positive impact on the low proportion of loneliness in this study. However, the result of this study is higher than studies conducted in Finland-32% [30], Canada-20% [28], and the United Kingdom-27% [12]. The possible explanation for the discrepancy might be due to variations in measuring the outcome variable and participant's characteristics.…”
Section: Discussioncontrasting
confidence: 75%
“…This will have a positive impact on the low proportion of loneliness in this study. However, the result of this study is higher than studies conducted in Finland-32% [30], Canada-20% [28], and the United Kingdom-27% [12]. The possible explanation for the discrepancy might be due to variations in measuring the outcome variable and participant's characteristics.…”
Section: Discussioncontrasting
confidence: 75%
“…Particularly, mothers staying at home with young children have been identified as a high-risk population for loneliness [ 4 , 5 ]. One previous longitudinal study showed the prevalence of loneliness among mothers was between 34 and 38% [ 6 ], and it was associated with both mothers’ depression and children’s adjustment [ 6 , 7 ]. The stability of mothers’ social and emotional loneliness was high from pregnancy until their child was 18 months old [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors considered to contribute to loneliness include perceived deviations from social 'norms' and perceived discrepancy between idealised and actual notions of motherhood both of which were identified with by the mothers in this study (Lee et al, 2017). Loneliness is considered a salient emotion found in motherhood (Yantzi et al, 2007) and the degree of loneliness felt correlates with a smaller social network, and psychological distress (Mandai, Kaso, Takahaski & Nakayama, 2018;Hawthorne, 2008;Luoma, Korhonen, Salmelin & Tamminen;. A pilot study revealed that offering regular support seemed to impact positively on mothers' mental health and on her relationship with her baby (Cust, 2016) and therefore extending support to mothers who are socially isolated may prevent feelings of loneliness and psychological distress.…”
Section: Lonelinessmentioning
confidence: 85%